Analisis Struktur Naratif dan Nilai Pendidikan Karakter dalam Film Mars (Mimpi Ananda Raih Semesta) Karya Aishworo Ang serta Pemanfaatannya sebagai Bahan Ajar di SMA - Puspita, Tita (Jurnal Artikula, 2022)
This study aims to identify and describe data about "The Narrative Structure and Value of Character Education in the film MARS (Mimpi Ananda Raih Semesta) by Aishworo Ang and its use as teaching materials in high school". This study uses descriptive qualitative research methods. The data obtained in this study are in the form of sentences in the form of conversations between characters. The source of data in this study is the conversation in the film. The data collection technique used the note-taking technique. The data analysis technique used the content analysis method (content analysis). The results of this study are the narrative structure and the value of character education. The narrative structure is 1). orientation, 2). complications, 3). resolution and 4). code while the value of character education is 1). religious, 2). honestly, 3). hard work, 4). love the motherland, 5). appreciating achievements, 6). social care and 7). responsibility. Implementation of Narrative Structure and Character Education Values in Aishworo Ang's MARS Film as Teaching Materials in SMA Class XI 2013 Curriculum in KD 3.18 identifies storylines, chapter by act and conflicts in dramas that are read or watched. The validation in this study shows that the narrative structure and character education values in Aishworo Ang's MARS film are worthy of being used as Indonesian language learning materials in high school.